Spectrum of paediatric rheumatic diseases in Nigeria - Olaosebikan, Babatunde Hakeem (Pediatr Rheumatol Online J, 2017)
BACKGROUND: Paediatric rheumatology service in Sub-Sahara African is virtually not available as there is a shortage of paediatric rheumatologists and other rheumatology health professionals. We aim to describe the clinical spectrum and the frequencies of paediatric rheumatic diseases (PRDs) in Lagos State University Teaching Hospital (LASUTH), Lagos, Nigeria. METHODS: This is a retrospective review of patients with PRDs seen over a five year period (March 2010 to February 2016) at the rheumatology clinic and children ward of LASUTH. We reviewed the folders of 57 patients from our records. The demographics, baseline laboratory features, clinical diagnosis, treatment patterns and patient outcomes were extracted and analyzed. Clinical and laboratory characteristics between patients with Juvenile idiopathic arthritis (JIA) and patients with juvenile connective tissue diseases (JCTD) were compared using Fisher’s exact test. RESULTS: Fifty seven patients were studied with a female to male ratio of 3 to 1 (Female: 43; M: 14). The mean age at presentation in years was 14 ± 4.4 years (range: 1.5–22 years). The mean duration of symptoms before diagnosis was 18.4 ± .9 months (range: 2–60 months). The diagnostic types of PRDs included 28(49.1%) cases of JIA. These were made up of 14 cases of polyarticular JIA, nine cases of oligoarticular JIA and 5 cases of systemic onset JIA. Others were 18 (24.6%) cases of juvenile systemic lupus erythematosus (JSLE), 3 (5.3%) cases of joint hypermobility syndrome, 2 (3.5%) cases of juvenile systemic sclerosis, 2 (3.5%) cases of fibromyalgia, 2 (3.5%) cases of plantar fasciitis, 1 (1.6%) case of juvenile dermatomyositis (JDM), 1 (1.6%) case of juvenile polymyositis-systemic lupus erythematosus (PM-SLE) overlap, 1 (1.6%) case of secondary bilateral knee osteoarthritis from Blount disease, 1 (1.6%) case of secondary osteoporosis from childhood leukemia and 1 (1.6%) case of Osgood-Schlatter’s disease. Constitutional symptoms and extra-articular diseases were significantly more frequent among JCTD cases than among the JIA cases (Constitutional symptoms: 100% vs 83.3%, p = 0.003; extra-articular disease: 100% vs 10.7%, p = 0.001). The percentage mortality in this study was 10.5% while 20 (35.1%) of the patients were lost to clinic follow up. CONCLUSION: The pattern of PRDs observed in this study is similar to that described in South African and North American series but it differs from patterns reported in Asian series. Although hitherto largely unrecognized, PRDs may constitute a substantial cause of morbidity and mortality in black Africans.